2010
DOI: 10.1590/s1517-83822010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and alternative antifungal therapies to oral candidiasis

Abstract: Candida-associated denture stomatitis is the most common form of oral candidal infection, with Candida albicans being the principal etiological agent. Candida adheres directly or via an intermediary layer of plaque-forming bacteria to denture acrylic. Despite antifungal therapy to treat denture stomatitis, infection is reestablished soon after the treatment ceases. In addition, many predisposing factors have been identified as important in the development of oral candidiasis, including malnourishment, common e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
1
29
0
3
Order By: Relevance
“…Although it is almost universally described as dimorphic, C.a. 's cell morphology actually lies on a pleomorphic continuum, ranging from ovoid yeast cells to filamentous hyphae (1, 2, 12, 13, 27, 42). This yeast has developed specific mechanisms of virulence that allow it to colonize epithelial cells of the host for the purpose of invading deeper layers or influencing the body's defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is almost universally described as dimorphic, C.a. 's cell morphology actually lies on a pleomorphic continuum, ranging from ovoid yeast cells to filamentous hyphae (1, 2, 12, 13, 27, 42). This yeast has developed specific mechanisms of virulence that allow it to colonize epithelial cells of the host for the purpose of invading deeper layers or influencing the body's defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high relapse rates of classical topical antifungals, we hypothesized which antifungal protocol would be better for DS treatment [25,26]. According to the inclusion criteria, only two study trials on patients with DS focused on the treatment with topical and systemic antifungal [1].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy has been prescribed for DS in cases not responding to topical agents or in cases with presence of systemic factors, such as immunosuppression or diabetes [35][36][37]. Generally, the dentists are concerned about prescribing systemic antifungals because of the risk of side effects.36 Conversely, in vivo studies reported the efficacy of systemic antifungals with minimal or no side effects to treat patients with DS through [1,21,25,38]. Interestingly, a Spanish study on drug choice for oral candidiasis demonstrated the strong predilection for topical drugs (miconazole and nystatin) by general dentists while the experts, including stomatologists frequently chosen systemic antifungals in the same cases [16].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of resistant strains has been increasingly reported in recent years. Candida albicans cells are highly resistant to antifungal agents such as fluconazole, nystatin, amphotericin B and chlorhexidine [6]. The cause of resistance could be extracellular enzymes such as proteinases, phospholipases, hemolysin and lipases because they facilitate adherence and penetration to the host [7].…”
Section: Introductionmentioning
confidence: 99%